2016
DOI: 10.1186/s13054-016-1253-1
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative blood pressure deficit and acute kidney injury progression in vasopressor-dependent cardiovascular surgery patients

Abstract: BackgroundIn vasopressor-dependent patients who had undergone cardiovascular surgery, we examined whether those with progression of acute kidney injury (AKI) had a greater difference (deficit) between premorbid and within-ICU hemodynamic pressure-related parameters compared to those without AKI progression.MethodsWe assessed consecutive adults who underwent cardiovascular surgery and who stayed in our ICU for at least 48 hours and received vasopressor support for more than 4 hours. We obtained premorbid and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
3
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 25 publications
2
52
3
2
Order By: Relevance
“…In addition, a retrospective study of 43,611 patients demonstrated that the occurrence of AKI in hospitalized, previously normotensive adults was independently associated with increased blood pressure during the first 2 years after discharge [21]. However, there are also reports that patients with hypotension are at an increased risk of developing renal failure, decreased renal perfusion aggravate renal function [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a retrospective study of 43,611 patients demonstrated that the occurrence of AKI in hospitalized, previously normotensive adults was independently associated with increased blood pressure during the first 2 years after discharge [21]. However, there are also reports that patients with hypotension are at an increased risk of developing renal failure, decreased renal perfusion aggravate renal function [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is a real clinical contradiction because all of these values are in agreement with the recommended target of the Surviving Sepsis Campaign [30]. In studies investigating abdominal hypertension, RPP is computed as MAP-IAP, while in some cardiological studies, the transrenal pressure gradient is defined as MAP-CVP and supposed to reduce renal blood flow [5, 12, 31, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…Elevated central venous pressure (CVP) and lower diastolic pressure were found in septic ICU patients with AKI in a retrospective study [11]. Another retrospective study conducted in mixed ICU patients showed that the mean perfusion pressure deficit (defined as MAP-CVP) and diastolic perfusion pressure deficit (CVP subtracted from diastolic arterial pressure) is associated with the worsening of renal function (shifts at least one KDIGO-stage) [12]. The elevated CVP has been reported as a stronger predictor of kidney function deterioration than cardiac index in a prospective study conducted in severe heart failure patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the sensitivity and specificity of echocardiography to diagnose pulmonary hypertension are modest [28,29]. Nevertheless, pulmonary hypertension and right-heart failure have emerged important risk factors for CSA-AKI, with venous congestion as the common cause [30,31]. Hence, future mechanistic studies investigating therapies mitigating preoperative PSPAP may offer protection against CSA-AKI.…”
Section: Relationship With Previous Studiesmentioning
confidence: 99%